Managing the Vietnam-China-United States Triangle - Womack, Brantly (VNU Journal of Science: Social Sciences and Humanities; Vol 32 No 1S, 2016)
Triangular international relationships are difficult to manage because every action produces simultaneous reactions from the two partners.  It is more difficult to predict simultaneous reactions, and if an unexpected and undesirable result occurs it is more difficult to correct. While each side pursues its own interest, managing triangular uncertainties becomes a major concern.  The Vietnam-China-United States triangle is especially complex because of its asymmetries, though it has some basic similarities to the general X>Y>Z asymmetric triangle. The U.S. is global but no longer hegemonic, China has become the major regional Asian power, and Vietnam is an important neighbor of China and member of ASEAN. For Vietnam, the triangle presents opportunities for leverage, but also risks of alienating one side or the other. Vietnam’s past history of participation in triangles has shown mixed results, but Vietnam has been successful in its management of the Vietnam-U.S.-China triangle since 2001. Economic relations with both have improved. Security and sovereignty issues cause tensions, but they have been handled by triangular management. Triangles do not exist in isolation from other relationships. Depending on the issue, tensions within a triangle can be managed focusing on the problem and bringing in more states that share the problem. Non-traditional security issues are an example. ASEAN is also useful because in many respects it can attract more global and regional attention than any one member. Global regimes such as the UN and WTO can also be used to take the pressure off of triangular tensions.